Impact of fluorine-18-fluorodeoxyglucose PET/computed tomography in staging of patients with gallbladder cancer: a systematic review and meta-analysis - Parida, Girish Kumar; Panda, Raj Abhisek; Agrawal, Kanhaiyalal (Nuclear medicine communications, 2021)
Fluorine-18-fluorodeoxyglucose (18F-FDG) PET/computed tomography (CT) has proven its efficacy in various malignancies; however, currently it is not used routinely for the management of gallbladder carcinoma (GBCa). So, we tried to review and analyze the impact of FDG PET/CT in the staging workup of gallbladder carcinoma. Databases like PubMed, SCOPUS, and EMBASE were searched for published original studies on F-18 FDG PET/CT in staging workup gallbladder carcinoma till December 2020. The included studies were assessed using the Revised Tool for the Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) checklist. A random-effect model was used for calculating pooled estimates of sensitivity and specificity. They were demonstrated in Forest plots. I2 statistic was used to assess heterogeneity in the studies. There is a paucity of literature with respect to the role of FDG PET/CT in GBCa. With the available data, the pooled sensitivity and specificity of 18F-FDG PET/CT for detection of local disease estimates of 96% [95% confidence interval (CI), 90-99%] and 91% (95% CI, 77-98%), respectively. Pooled sensitivity and specificity for detection of metastatic disease are 95% (95% CI, 88-98%) and 97% (95% CI, 90-100%), respectively. For nodal disease, these values are 75% (95% CI, 53-90%) and 91% (95% CI, 77-98%), respectively. Besides this, FDG PET/CT findings have changed the management in significant proportion of patients. With the limited data available currently, we found that 18F-FDG PET/CT is a quite accurate noninvasive tool in staging the workup of GBCa. However, further large multicentre trials are necessary for the generation of stronger evidence in this regard.